Targeted metagenomics of active microbial populations with stable-isotope probing. (October 2016) - Coyotzi, Sara; Pratscher, Jennifer; Murrell, J Colin; Neufeld, Josh D
Graphical abstract: Highlights: Stable-isotope probing enables targeted metagenomics. Genomes and functions accessed from active and uncultivated microorganisms. High-throughput screens and genome assemblies possible via DNA-SIP and metagenomics. Abstract : The ability to explore microbial diversity and function has been enhanced by novel experimental and computational tools. The incorporation of stable isotopes into microbial biomass enables the recovery of labeled nucleic acids from active microorganisms, despite their initial abundance and culturability. Combining stable-isotope probing (SIP) with metagenomics provides access to genomes from microorganisms involved in metabolic processes of interest. Studies using metagenomic analysis on DNA obtained from DNA-SIP incubations can be ideal for the recovery of novel enzymes for biotechnology applications, including biodegradation, biotransformation, and biosynthesis. This chapter introduces metagenomic and DNA-SIP methodologies, highlights biotechnology-focused studies that combine these approaches, and provides perspectives on future uses of these methods as analysis tools for applied and environmental microbiology.